Hyponatraemia in heart failure. Issue 6 (14th June 2020) - Tee, Su Ling; Sindone, Andrew; Roger, Simon; Atherton, John; Amerena, John; D'Emden, Michael; Erlich, Jonathan; De Pasquale, Carmine
Abstract: Hyponatraemia is common in heart failure (HF). It is estimated that over 20% of patients admitted to hospital with HF have hyponatraemia. It has also been repeatedly shown to be a surrogate marker of increased morbidity and mortality in this specific population. This review focuses on the pathophysiology of hyponatraemia through the activation of neurohormonal cascades in HF, the clinical implications of sustained hyponatraemia and treatment options in the management of this challenging phenomenon.